Computer program development for the analysis of inelastic beam and soil behaviour in geotechnical design - Howie, C T (Department of Civil Engineering, 2016)
Computer-aided engineering requires the correct implementation of design methods in computer programs so as to play a beneficial role in engineering practice. This thesis describes the development of a computer program to analyse geotechnical engineering problems based on the principles of beam-soil interaction where the beam is supported by a single or two-layer soil system. In 1867, a foundation model was proposed by Winkler in which the elastic foundation beneath a horizontal beam could be viewed as a series of independent springs. Foundation reaction to beam deflection is, therefore, linear. A stiffness matrix, for use in matrix methods of structural analysis, has been developed to define this beam-soil interaction, and such a method can be incorporated into a computer program. Furthermore, an iterative technique was created to allow for inelastic soil response when using the elastic stiffness matrix. However, such a technique did not consider realistic soil behaviour, and has limitations is used for practical design. This research' work describes how use can be made of the pressure-displacement response relationship for a soil to bring greater realism to beam-soil modelling and analysis. Such a relationship is commonly determined in geotechnical design procedures through a plate load test in the field. In addition, the iterative technique is extended to include non-linear beam behaviour as well, and plastic hinging of the beam material is incorporated to enable limitation of inelastic response. While previous research has only considered foundations of a single soil only, a procedure to model a two-layered system is developed. Two-layered foundations are required for proper modelling of soldier pile support systems, an area of structural design in geotechnics chosen to demonstrate realistic design potential for the computer program. The two-layered principle is based on the derivation of a control parameter to differentiate between response from just the upper soil layer, and a combined response from both soil layers. The procedure is relatively simple, and no extra information is required other than the two pressure displacement relationships for the individual soil layers. A desktop computer program is described which incorporates the inelastic analysis features, as well as the two-layered soil system. The program makes use of a graphical user interface to offer the user an easy, interactive environment for analysing beam-on-soil foundation problems. As such, the program can be used directly, or for further research into beam-soil interaction. The program is applied in the analysis of both field and laboratory tests to ascertain its accuracy in predicting beam-soil interaction. The laboratory test measures the deflection of a horizontal beam on a single soil foundation medium, where the beam is loaded by a single jack at approximately mid-span. Computer predictions for such a test were in very close agreement with the laboratory observations, despite the small magnitude of beam displacements, and the fact the beam-soil system suffered a bearing capacity failure which affected the beam deflection. The field test was performed to investigate the performance of a flexible soldier pile under high anchor loading. Results of the computer analyses again show the program's predictions to be in very close agreement with the field measurements. Currently, the program does not include the facility to model soil layers behind a soldier pile, but the method developed in this thesis can easily incorporate multiple pressure-displacement curves for different soils. Final conclusions drawn express a need for more research into soldier pile systems before the techniques of this work can be used for routine design. Nevertheless, the development of the program has made a significant contribution to advancing the use of computer-aided design in this field of geotechnical engineering.